The Onset of the Fetal Respiratory Rhythm: An Emergent Property Triggered by Chemosensory Drive? - Eugenin-Leon, J; Beltran-Castillo, S (Springer New York LLC, 2017)
The mechanisms responsible for the onset of respiratory activity during fetal life are unknown. The onset of respiratory rhythm may be a consequence of the genetic program of each of the constituents of the respiratory network, so they start to interact and generate respiratory cycles when reaching a certain degree of maturation. Alternatively, generation of cycles might require the contribution of recently formed sensory inputs that will trigger oscillatory activity in the nascent respiratory neural network. If this hypothesis is true, then sensory input to the respiratory generator must be already formed and become functional before the onset of fetal respiration. In this review, we evaluate the timing of the onset of the respiratory rhythm in comparison to the appearance of receptors, neurotransmitter machinery, and afferent projections provided by two central chemoreceptive nuclei, the raphe and locus coeruleus nuclei. © Springer International Publishing AG 2017.